AB0850-HPR Side effect profile in patients with rheumatoid arthritis on leflunomide with and without loading dose. (23rd January 2014) - Arava, S.; Uppuluri, R. R.; Fatima, F.; Mohiuddin, M. Y.; Rani, A.; Kumar, D.; Challa, S.; Jonnada, S.; Sri Purna, D.
Abstract : Background: Leflunomide (LEF) a pyrimidine synthesis inhibitor is a disease modifying antirheumatic drug (DMARD) in rheumatoid arthritis (RA). In combination with methotrexate (MTX), it may prove superior to either agent alone. Side effects such as diarrhoea, skin rash, alopecia and hepatitis were observed more in the patients of RA when given leflunomide with loading dose (100mg/d for 3 days). It is considered that the side effects would be lesser when the patients are not given the loading dose of leflunomide. In our study we compared the side effect profile in two cohorts where in one was given loading dose the other did not Objectives: To evaluate the side effects observed in patients receiving LEF as an add on therapy with or without loading dose in RA Methods: Three hundred eighty seven patients with active RA without a loading dose of LEF(ARAVA) in combination with MTX were included. The indication to start LEF was suboptimal response to MTX. Hemogram, ESR/CRP and LFT were measured both at entry and monthly for the first six months and every three months thereafter. LEF tolerability was closely monitored and adverse events were noted and followed up. A historic comparison was done with the study conducted at the same centre earlier between October 2001 and December 2003(Firdaus, Rao). Results: A total of 387 patients of which 332 women (85.7%) and 57 men (14.7%), with a mean age 49.7±10.71 yrs and drug dosage duration of 6 ± 4.2 yrs were included; 319 (82.4%) patients were seropositive. The side effect profiles were depicted in table -1 Conclusions: The mild side effects may be same with LEF with or without loading dose but serious adverse events may be more common with loading dose. It looks that depriving the loading dose for the patients may not reduce the side effects which are possibly due to LEF. References: BykerkV.P. et al Canadian recommendations for the management of RA. J Rheum 2012;39:1559-15982. ErraA. et al Is the recommended dose of LEF the best regimen to treat RA patients? ( L) Rheumatology2003; 42: 1123-1124. MaddisonP. et al LEF in RA: Recommendations through a process of consensus. Rheumatology 2005;44:280-286. Rao URK, Fatima F. LEF as an add on therapy in RA- Adverse events. EULAR 2004 Abstract FRI0120. Disclosure of Interest: None Declared